The History of White-Brazilian Art and the Limits of Black Humanity - Amancio, Kleber Antonio de Oliveira Amancio (Farol, 2021)
This article aims to present the concept of white-Brazilian art history from a critical reading of the tradition erected by an epistemologically Eurocentric art literature. Based on this diagnosis, we intend to point out paths for the construction of a democratic environment to incorporate narratives that were obliterated by the colonial project.